Cell Membrane‐Inspired Graphene Nanomesh Membrane for Fast Separation of Oil‐in‐Water Emulsions (Adv. Funct. Mater. 31/2022). (1st August 2022) - Liu, Yanan; Coppens, Marc‐Olivier
Abstract : Graphene Nanomesh Membranes In article number 2200199, Yanan Liu and Marc‐Olivier Coppens leverage the mechanisms underpinning selective, high water permeation and anti‐fouling of cell membranes, to create an artificial membrane, based on chitosan‐functionalised graphene nanomesh, for tricky oil/water separations within a wide pH range and at very high water flux (±4000 L/m 2 h).